Spiritual mindfulness in supporting pregnant women for the prevention of low birth weight - Septiana Juwita; Indah Risnawati; Ummi Kulsum; Dwi Astuti; Ana Zumrotun Nisak (STIKES Mamba'ul 'Ulum Surakarta, 2026)
Background: Spiritual mindfulness plays a role in reducing pregnancy-related stress and supporting favorable birth outcomes, thereby representing a potential strategy for prevention of low birth weight (LBW). The aimed to analyze necessity for spiritual mindfulness among pregnant women as an effort to prevent LBW. Methods: A qualitative designed with a phenomenological approach to explore subjective meanings, lived experiences, and spiritual mindfulness practices of pregnant women in relation to LBW prevention. Participants were selected using purposive sampling based on predefined inclusion and exclusion criteria. Key informants were pregnant women who met the eligibility criteria, while village midwives served as the main subjects, and community health volunteers acted as supporting informants. Data were collected through Focus Group Discussions (FGDs). Instruments study included researcher as primary instrument, a semi-structured interview guide, and informed consent forms. Data analysis used thematic analysis. Validity was ensured through the application of trustworthiness criteria. Results: LBW cases are still present and associated with various maternal and obstetric risk factors, particularly hypertensive disorders of pregnancy, anemia, premature rupture of membranes, and chronic energy deficiency. Psychosocial factors also contribute to risk of LBW. Maternal stress and anxiety, especially in unplanned pregnancies, may adversely affect maternal and fetal health. Social support from family members and supportive approaches from healthcare providers emerged as important protective factors in maintaining maternal well-being. Additionally, they demonstrated limited understanding of LBW. Conclusion: Spiritual mindfulness emerged as a psychosocial necessity that supports pregnant women in managing stress, enhancing inner calmness, and promoting positive health behaviors during pregnancy.